Exploring English Learning on Non-Formal Education as an Effort to Enhance Students Speaking Ability - Muhammad Danial; Sari, Nila; Nurhaeni; Fajriani; Farhanuddin (LETS: Journal of Linguistics and English Teaching Studies, 2023)
Non formal education can improve learners’ capacity in any skill. This study is aimed to reveal the implementation of English learning in MOEC Majene as a non-formal education unit and how students’ perception toward its learning were. This study used quantitative method with descriptive data. The       participants of this study were students of English Education from Unsulbar University and STAIN Majene  who were selected using a purposive sampling technique in which they are students in MOEC Majene who wish to develop their English capacity even though they are English education students in university. The research data was obtained by using observation, interviews, and questionnaires. The results of this study indicated that English education  students from Unsulbar University and STAIN Majene had low speaking ability before enrolling in the  MOEC Majene. The findings showed that MOEC Majene gave powerfull impact on speaking skills of English  education students in Unsulbar University and STAIN Majene. The researchers also discovered that learning environment at MOEC Majene could assist students in improving their communication skills. Students’ responses draw the description of how MOEC Majene has impressed learners there.